Interview with Wm. Brad O’Dell - Todd Skelton (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2010)
Wm. Brad O’Dell is a 2009 UT graduate and received a B.A. in College Scholars Program with an emphasis in Structural Chemistry. College Scholars is a highly selective honors program major for students with interdisciplinary interests. Brad was also in the Chancellor’s Honors Program and received numerous accolades for his academic achievement throughout his career at the University of Tennessee, including the prestigious Barry M. Goldwater Scholarship in 2008. Brad now lives between Cambridge, UK and Bethesda, MD as a student in the National Institutes of Health-Oxford-Cambridge Graduate Partnership Program.
Keywords: Undergraduate Research; Pursuit